Pathological and molecular findings of visceral gout caused by Israel variant 2 (IS/1494/06) genotype of infectious bronchitis virus in chickens - Timurkaan, Necati; Ongor, Hasan; Kalender, Hakan; Karabulut, Burak; Coven, Fethiye; Cevik, Aydin; Cetinkaya, Burhan (Ankara Univ, 2023)
The aim of this study was to investigate pathological lesions and the presence of of Israel variant 2 (IS /1494/06) genotype of infectious bronchitis virus (IBV) in chickens with visceral gout. Sudden deaths were observed in broiler breeders and layer hens belonging to two different flocks located in eastern Turkiye. Broiler chickens were previously vaccinated with a vaccine containing strains of IBV Massachusetts serotype, but no information was available about the vaccination history of laying hens. At necropsy, there was accumulation of white chalk-like material on the serosal surface of the heart, liver, spleen and air sacs. The kidneys were unilaterally or bilaterally enlarged and pale in color and, ureters were also enlarged. Pooled organ samples from diseased chickens and kidneys alone were examined by virus isolation, real-time reverse transcription polymerase chain reaction (rRT-PCR), nucleotide sequencing analysis and histological methods. Israel variant 2 genotype of IBV was detected in the samples of both flocks as a result of virus isolation, rRT-PCR and DNA sequencing analysis. Histological examination revealed multifocal and randomly distributed crystal deposits in the renal tubulus and adjacent interstitium. Mild to moderate crystalline deposits surrounded by heterophils and macrophages were detected in the serosal layers of the heart, spleen, liver, and air sacs. The findings of this study indicated that IBV should be taken into consideration in visceral gout cases of chickens, and detection of IBV genotypes in the field will enable us to use vaccines compatible with these genotypes in order to control the disease more efficiently.
Keywords: Chicken; Israel variant 2 genotype; Infectious bronchitis vir?s; Pathology; Visceral gout